Management of biobanking for medical genetics research - V. Yu. Tabakov (Кардиоваскулярная терапия и профилактика, 2022)
Biobanking is one of the most important elements of the modern infrastructure for biomedical research. Organization of a biobank on the basis of the N. P. Bochkov Medical Genetics Research Center provides a centralized infrastructure for preparing biomaterial for research. Biobank has the format of a research equipment sharing center and works with two types of unique biomaterials from patients with genetic diseases: blood/blood components and vital cells of various tissue origin. The storage facility of the Biobank is equipped with low-temperature (-80° C) and cryostorage (-196° C) systems. Identification and search of samples is carried out using a bar-coding system and is implemented through the information interface of the biobank, which is integrated into the general database of patients at the Medical Genetics Research Center. Information on biomaterial samples is presented in periodically updated catalogs on the page of equipment sharing center “Biobank”. Biobank collection is available to internal and external users.